Cash Flow Analysis for Financial Control in the SDN 6 Kuta Building Construction Project - I Gede Wahyu Adi Putra; Ida Ayu Cri Vinantya Laksmi; Kadek Windy Candrayana (Jurnal Ilmiah Telsinas, 2026)
The construction industry plays a significant role. Construction projects carry a high level of risk, particularly in financial management and in balancing cash flow between revenue and expenditure. This study aims to analyze cash flow and evaluate the financial condition of the SDN 6 Kuta building construction project based on the schedule. The method used is descriptive quantitative, utilizing secondary data in the form of the Implementation Budget Plan, time schedule, and project progress reports. The results indicate that the project's Implementation Budget Plan Rp 1,975,413,914, with a payment system in installments and a 10% down payment. An analysis of the existing cash flow indicates a cash flow imbalance. In some periods, particularly until the middle of the project, cash outflows exceeded cash inflows, resulting in a deficit (overdraft), requiring the contractor to use personal funds to maintain the project. The implementation of alternative policies, such as increasing the down payment to 25% and adding additional funding sources, resulted in a more stable cash flow pattern, with cash receipts tending to exceed expenditures for most of the project period. Although the profit under the existing policy is higher at 12.58% compared to the alternative policy at 9.45%, the alternative policy is considered more optimal because it reduces the risk of overdrafts and improves the project's financial stability. Therefore, proper cash flow management through adjustments to payment systems and funding strategies significantly impacts the success of construction projects, not only in terms of profitability but also in terms of liquidity and project sustainability.